Mucormycosis in Uncontrolled Diabetic: A Case Report - Sadeghi 1, Farangis; Hajian 2, Mahtab; Batti 3, Badie; Mohammadi 2, Zeinab; Noyani 1, Amir (Shahroud Journal of Medical Sciences, 2019)
Background: Mucormycosis is an opportunistic infection produced by various fungi in the order Mucorales, which is most commonly seen in people with a defect, especially diabetics. Introduction of this infection can involve processes such as insulin injections and tooth extractions. Mucormycosis mortality is significantly high even with surgical treatment and management of diabetes. In this paper, a case of 28-year-old female with a history of Type 1 Diabetes Mellitus referred to emergency ward 5 days after tooth extraction experiencing a progressive pain and swelling was reported. Patient's examinations showed left orifice edema, left 7th nerve paralysis, and ocular-paralysis of 3rd, 4th and 6th on the left side. The patient was deployed to a more equipped facility in Mashhad (Iran), and after several days she died.